Thematic Teaching Materials based on Riau Local Wisdom - Miftahul Jannah; Zaka Hadikusuma Ramadan (Jurnal Ilmiah Sekolah Dasar, 2021)
Learning was the process of interaction between students and learning resources. Learning resources should support good interaction. One of the learning resources was teaching materials. Teaching materials will make students learn more structured and can motivate. But today, there were still few who make thematic teaching materials. The aims of this research is to create thematic teaching materials based on Riau local wisdom. The type of research conducted was R&D with 4D Â models. The subjects of this study were 6 experts, consisting of 2 material experts, 2 linguists and 2 design experts. The data collection methods were interviews and validation sheets. The analysis was qualitative and quantitative analysis of interview data and validation sheets. The study results stated that the thematic teaching materials based on Riau local wisdom are worth seeing from the material, language, and design aspects with an average score of 93% with very valid category. So, thematic teaching materials based on local wisdom of Riau are worth using.